Very good lives : the fringe benefits of failure and the importance of imagination - Rowling, J. K. (Little, Brown and Company, 2015)
In 2008, J.K. Rowling delivered a deeply affecting commencement speech at Harvard University. Now published for the first time in book form, VERY GOOD LIVES presents J.K. Rowling's words of wisdom for anyone at a turning point in life. How can we embrace failure? And how can we use our imagination to better both ourselves and others? Drawing from stories of her own post-graduate years, the world famous author addresses some of life's most important questions with acuity and emotional force.